Synthesis and Development of Suitable Method for New Thiadiazoles using Hydrazonoyl Halides - Alarbash, Munirah F.; Al-Faiyz, Yasair S.; Wiggins, Jeffrey S.; Sayed, Abdelwahed R. (Current Organic Synthesis, 2025)
BackgroundHydrazonoyl halides and methylhydrazinecarbodithioate have been generally utilized in the synthesis of heterocycles.MethodsThis study describes a new and simple method to prepare new thiadiazoles from the reaction of N-(naphthalen-1-yl)-2-oxopropanehydrazonoyl chloride or ethyl 2-chloro-2-(2-(naphthalen-1-yl)hydrazono)acetate with methylhydrazinecarbodithioate in the presence of basic medium under reflux. In this study, the synthetic schemes are designed to show the chemical reactions. Elements analysis, Fourier Transform Infrared Spectroscopy (FT-IR), Mass Spectrometry (MS), and Nuclear Magnetic Resonance (NMR) are used to identify and characterize the final compounds.ResultsThere are two ways to synthesize the final thiadiazoles molecules. The first can be through nucleophile substitution of thiolate of methylhydrazonecarbodithioate to the chlorinated carbon of hydrazonoyl. Hydrochloric acid is then removed to provide an S-alkylated intermediate. Methanethiol is eliminated from this intermediate by an in situ intramolecular cyclocondensation process to give the final products. The subsequent [3+2] cycloaddition involving 1,3-dipolar cycloadditions of nitrilimines to C=S is succeeded by the removal of methanethiol.ConclusionThis approach utilizes affordable, readily accessible reagents and simple reaction conditions to produce new thiadiazole derivatives with satisfactory yields.
Keywords: Hydrazonoyl